Single-center analysis of servo-controlled cooling during the transport of neonates with perinatal asphyxia - Huang, Lingzhu; Su, Qiru; Huang, Weimin; Lu, Xueling; Chen, Yu Lan; Yang, Xue; Jiang, Jingbo (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the safety and efficacy of servo-controlled cooling during the transport of neonates with perinatal asphyxia.MethodsWe conducted a retrospective non-randomized case-control study at a single-center,which included 65 neonates diagnosed with Hypoxic-Ischemic Encephalopathy (HIE). These neonates were referred by the Shenzhen Children's Hospital medical transport team between January 2020 and June 2024. All subjects received 72 h of mild hypothermia treatment upon admission. Participants were categorized into an active group and a control group based on the use of servo-controlled cooling during transport. To evaluate differences in clinical characteristics, transport variables, and hospitalization outcomes between the two groups, we employed independent samples t-tests, Mann–Whitney U tests, and χ2 tests for inter-group comparison.ResultsAmong the 65 subjects, there were 42 males and 23 females. The active group comprised 17 patients, while the control group included 48. No statistically significant differences were observed in sex, gestational age, birth weight, or HIE grade between the two groups (P > 0.05). In comparison to the control group, the active group experienced a shorter duration from leaving the referral center to reaching the target temperature (1 h vs. 2.67 h, Z = −4.513, P < 0.05), arrived at the treatment center at a lower temperature (34.03°C vs. 35.6°C, t = −4.991, P < 0.05), and demonstrated a higher proportion of patients within the target temperature range upon arrival [88.2% (15/17) vs. 16.7% (8/48), χ2 = −0.774, P < 0.05]. Additionally, the length of hospitalization was shorter for the active group (15 days vs. 19 days, Z = −2.835, P < 0.05). The proportion of patients in the severe range on the aEEG recorded on the third day of cooling was higher in the control group [45.8% (22/48) vs. 11.8% (2/17), Z = −2.042, P < 0.05].ConclusionActive therapeutic hypothermia during transport is both safe and feasible.It enables a more rapid and stable achievement of the target temperature, enhances short-term EEG outcomes, and may serve as the preferred method for transporting neonates with hypoxic-ischemic encephalopathy(HIE).